Processing of Tidal Records at Hout Bay Harbour - Merry, C. L. (The International Hydrographic Review, 2015)
Twenty-two years of tidal records at Hout Bay Harbour in South Africa have been digitized and analysed in order to seek long-term variations in mean sea level. After accounting for a local movement of the tide gauge, a rise in sea level of approximately 1 mm per year has been detected. This agrees well with global estimates of the eustatic rise in sea level.